Merdeka Belajar, Merdeka Berpikir, Analisis Respon Mahasiswa terhadap Program MBKM: Independent Learning, Independent Thinking, Analysis of Student Responses to the MBKM Program - Rio Brandlee; Kartina Rahmadhani Rambe (ITScience (Information Technology and Science), 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) program is an innovative policy that provides learning flexibility through various practical activities, such as internships, humanitarian projects, and student exchanges. This policy offers significant benefits, but its implementation faces various challenges, especially regarding understanding, administration, and socialization. This study aims to analyze students' responses to MBKM, focusing on their satisfaction, understanding, and perception of the program's relevance to the world of work. This study uses a mixed methods approach that combines quantitative surveys and qualitative interviews. The survey was conducted on 50 STKIP Pangeran Antasari students using a closed questionnaire with a Likert scale of 1-5. In addition, in-depth interviews were conducted to gain more detailed insights into students' experiences. The results showed that the satisfaction aspect had an average score of 4.1, with 82% positive responses, reflecting students' appreciation of the program's flexibility. The perception aspect was also high, with an average score of 4.0 and 80% positive responses, indicating the program's relevance to the needs of the world of work. However, the understanding aspect had a lower score, namely 3.8, with 24% negative responses, reflecting the lack of socialization and administrative complexity as the main challenges.In conclusion, MBKM significantly improves students' skills and relevance to the world of work. However, increasing socialization and simplifying the administrative process are necessary to optimize its implementation. This study provides strategic recommendations to improve the quality of MBKM implementation and ensure that students can optimally benefit from the benefits.